A 970-year-long summer temperature reconstruction from Rogen, west-central Sweden, based on blue intensity from tree rings - Fuentes, Mauricio; Salo, Riikka; Bjorklund, Jesper; Seftigen, Kristina; Zhang, Peng; Gunnarson, Bjorn; Aravena Donaire, Juan Carlos; Linderholm, Hans W. (My University, 2018)
To assess past climate variability in west-central Scandinavia, a new 972-year-long temperature reconstruction, based on adjusted delta blue intensity (BIadj), was created. Presently, it is the longest blue intensity chronology in Fennoscandia and the third longest in the northern hemisphere. Measurements were obtained from 119 tree line Scots pine (Pinus sylvestris L.) samples from Rogen, in the central Scandinavian Mountains, Sweden. Early and latewood blue intensity absorption data were used to create BIadj. The data were detrended using a signal-free regional curve standardization method (RSFi) to minimize biological noise and maximize low-frequency climate information. The Rogen BIadj chronology has a substantially stronger temperature signal at inter-annual timescales than the corresponding tree-ring width (RW) chronology, and it displays good spatial representation for the south-central parts of Scandinavia. The BIadj summer (June through August) temperature reconstruction, extending back to 1038 CE, exhibits three warm periods in 1040-1190 CE, 1370-1570 CE and the 20th century and one extended cold period between 1570 and 1920 CE. Regional summer temperature anomalies are associated with a Scandinavian-Greenland dipole sea-level pressure pattern, which has been stable for the past several centuries. Major volcanic eruptions produce distinct anomalies of BIadj indices indicating cooling of summer temperatures in the subsequent years. Our results show that BIadj from Pinus sylvestris in Scandinavia is a suitable proxy providing opportunities to explore past temperature variability at various frequencies, atmospheric dynamics and variability in external forcing. Nevertheless, long-term trend differences with RW imply that further research is needed to fully understand the application of this technique in dendroclimatology.
Keywords: 1000 years; blue intensity; mxd; pinus sylvestris l; scandinavia; temperature reconstruction; tree rings